Kedudukan Filsafat Sebagai Landasan Pengembangan Teori Manajemen Pendidikan Islam - Taufiq, Muhammad; N, Abd. Muid (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The development of Islamic Education Management (IEM) theory requires a strong philosophical foundation so that it does not get caught up in adopting secular management models that ignore Islamic values. This study aims to analyse the role of Islamic philosophy as the main foundation in formulating a value-based theoretical framework for IEM. The research uses a conceptual study method with a philosophy of science approach, specifically through the Trinity of Philosophy of Science framework, which includes ontology, epistemology, and axiology. The results of the study show that ontologically, Islamic philosophy views humans as khalifah fil ardhi and educational organisations as spaces of service, which underlies the servant leadership model. Epistemologically, MPI requires the integration of sources of knowledge from revelation (bayani), reason (burhani), and intuition (irfani) to overcome the dichotomy of knowledge and encourage the development of a transdisciplinary curriculum. Axiologically, MPI is oriented towards the values of amanah, ihsan, and syura with the ultimate goal of falah, which is measured through the maqashid syariah framework. This study concludes that Islamic philosophy is a key prerequisite in the development of MPI theory to realise a value-based education management system capable of responding to the challenges of modernisation without losing its Islamic identity.